Obstacling Factors the Role of Sharia Banking in Achieving SDGS1 (No Poverty) as a Sustainable Development Goal - Sandra Dewi; Yaswirman Yaswirman; Rudi Febriamansyah; Henmaidi Henmaidi (Kontigensi : Jurnal Ilmiah Manajemen, 2024)
The purpose of this study are factors that inhibit the role of Islamic banking in achieving SDGs1 (No Poverty) as a sustainable development goal in the city of Bukittinggi, West Sumatra. This research methodused is the application of the Delphi method which aims to obtain the agreement of experts who have high reliability values ​​through a series of questionnaires accompanied by feedback on the agreement. The Delphi method will be related to expert opinions with the aim of agreement with experts who have high reliability on mastery of learning design and ecoliteracy skills through a series of questionnaires accompanied by feedback on the agreement. The results of this studyare known that the factors that inhibit the role of Islamic banking in achieving SDGs1 (no poverty) as a sustainable development goal stakeholders do not agree with the Demographic Culture factor because people know the existence of Indonesian sharia bank BSI Bukittinggi City has strong legal force. For the SME factor, all stakeholder respondents did not agree with the Hobby factor because many hobby factors did not provide a background for MSE Pekaku Bukittinggi City but as an economic added value. Therefore, a consensus was obtained that in BSI Bukittinggi City, namely the Demographic Culture factor and in SMEs, the hobby factor is not used because these factors are not 86 influential in the development of SDGs1 (no poverty) achievement centers as public spaces in the research area.